Layered Transition Metal Sulfides for Supercapacitor Applications - Ozan Öztürk; Prof. Dr. Emre Gür (ChemElectroChem, 2024)
Abstract Supercapacitor (SC) devices holds an important position between traditional capacitors and ion batteries in terms of energy density and power density values. In particular, SC′s greater power density values than Li‐ion batteries make them useful for some specific applications, such as storing energy in hybrid cars while the car slows down. Increasing energy density values is one of the key challenges for the SC community. Transition metal dichalcogenides (TMDCs), are one of the new developing important material systems to have this potential, compared to their counterparts’ transition metal oxides and conductive polymers. This review is about giving insight into the electrochemical performances of two‐dimensional (2D) layered transition metal sulfides (TMS) such as MoS2, WS2, TaS2, NbS2, VS2, TiS2 and ZrS2 materials. On the other hand, the methods mostly used in synthesizing these materials are presented.